Effect of alloying elements on microstructure, mechanical and damping properties of Cr-Mn-Fe-V-Cu high-entropy alloys. Issue 11 (November 2018) - Song, Ruokang; Ye, Fan; Yang, Chenxi; Wu, Sujun
Graphical abstract: Highlights: New Cr-Fe-Mn-V-Cu high-entropy alloys with a great balance between strength and ductility were designed and developed. Strong Mn-V interaction and immiscibility of Cu lead to formation of multi-phase solid solutions in the alloys. Excellent mechanical performance of CrMn0.3FeVCu0.06 alloy result from high density of dislocations and fine precipitates. Abstract: A series of new Cr-Mn-Fe-V-Cu high-entropy alloys were prepared by arc melting and suction casting. It is found that with the addition of Cu, the structure of the alloys evolved from BCC + BCC1 phases to BCC + FCC phases. With increase of Cu, the volume fraction of the Cu-Mn-rich FCC phase increased, and the morphology of the FCC phase transformed from granular particles to long strips and blocks. Compared with other reported HEAs, the Cr-Mn-Fe-V-Cu HEAs exhibit a good balance between strength and ductility. The CrMn0.3FeVCu0.06 alloy with granular FCC particles exhibits the highest compressive yield strength (1273 MPa) and excellent ductility ( ε f   =  50.7%). Quantitative calculations for different strengthening mechanisms demonstrate that dislocation and precipitate strengthening are responsible for high strength of the CrMn0.3FeVCu0.06 alloy, while the solid solution strengthening effect is very low because of its small atomic-size difference. In addition, the CrMn0.3FeVCu0.06 alloy exhibits good damping capacity due to its high dislocation and interface damping effects. Therefore, the dislocation density and distribution of FCC phase are the crucial factors for improvement of both mechanical properties and damping capacity of the HEAs.